Full stack development with JHipster : build full stack applications and microservices with spring boot and modern JavaScript frameworks /: build full stack applications and microservices with spring boot and modern JavaScript frameworks. (2020) - Sasidharan, Deepu K; N., Sendil Kumar
No abstract available